Involvement of soluble Fas Ligand in germ cell apoptosis in testis of rats undergoing autoimmune orchitis - Jarazo Dietrich, Sabrina Soledad (2012)
Experimental autoimmune orchitis (EAO) is a model of chronic inflammation and infertility useful for studying immune and germ cell (GC) interactions. EAO is characterized by severe damage of seminiferous tubules (STs) with GCs that undergo apoptosis and sloughing. Based on previous results showing that Fas–Fas Ligand (L) system is one of the main mediators of apoptosis in EAO, in the present work we studied the involvement of Fas and the soluble form of FasL (sFasL) in GC death induction. EAO was induced in rats by immunization with testis homogenate and adjuvants; control (C) rats were injected with adjuvants; a group of non-immunized normal (N) rats was also studied. Activation of Fas employing an anti-Fas antibody decreased viability (trypan blue exclusion test) and induced apoptosis (TUNEL) of GCs from STs of N and EAO rats, an effect more pronounced on GCs from EAO STs. By Western blot we detected an increase in sFasL content in the testicular fluid of rats with severe EAO compared to N and C rats. By intratesticular injection of FasL conjugated to Strep-Tag molecule (FasL-Strep, BioTAGnology) and its immunofluorescent localization, we demonstrated that sFasL is able to enter the adluminal compartment of the STs. Moreover, FasL-Strep induced GC apoptosis in testicular fragments of N rats. By flow cytometry, we detected an increase in the number of membrane FasL-expressing CD4+ and CD8+ T cells in testis during EAO development but no expression of FasL by macrophages. Our results demonstrate that sFasL is locally produced in the chronically inflamed testis and that this molecule is able to enter the adluminal compartment of STs and induce apoptosis of Fas-bearing GCs.